Correlations between functional performance, health-related quality of life, and parental impact on children with developmental delays. (June 2014) - Hsieh, Ru-Lan; Lin, Ming-I; Huang, Hsiao-Yuan; Lee, Wen-Chung
<x xml:space="preserve">Abstract</x> Objective: To examine the correlation of function, quality of life (QOL), and parental impact on developmental delayed children. Methods: Sixty parents of children with developmental delays (M:F = 36:24, mean age 4 years and 2 months) and 56 parents of age–sex matched typical development children were included. Pediatric Outcomes Data Collection Instrument and Child Health Questionnaire for children, World Health Organization-QOL, Impact on Family Scale, and Hospital Anxiety and Depression Scale for parents were assessed. Results: Functional performance was correlated with physical component of QOL in children (correlation coefficients: 0.7–0.9; p < 0.01), age of children (0.3–0.4; p < 0.05) and parents (0.3; p < 0.05), maternal employment (0.3–0.4; p < 0.05), parental QOL (0.3–0.4; p < 0.01), family impact (−0.3 to −0.5; p < 0.01), and parental emotion (−0.3 to −0.4; p < 0.05). Conclusions: Children who exhibited higher levels of function had higher QOL, as did their parents, and less parental impact.